Human embryonic stem cell derived mesenchymal progenitors express cardiac markers but do not form contractile cardiomyocytes. - Christophe M Raynaud; Najeeb Halabi; David A Elliott; Jennifer Pasquier; Andrew G Elefanty; Edouard G Stanley; Arash Rafii (PLoS ONE, 2013)
Mesenchymal progenitors or stromal cells have shown promise as a therapeutic strategy for a range of diseases including heart failure. In this context, we explored the growth and differentiation potential of mesenchymal progenitors (MPs) derived in vitro from human embryonic stem cells (hESCs). Similar to MPs isolated from bone marrow, hESC derived MPs (hESC-MPs) efficiently differentiated into archetypical mesenchymal derivatives such as chondrocytes and adipocytes. Upon treatment with 5-Azacytidine or TGF-β1, hESC-MPs modified their morphology and up-regulated expression of key cardiac transcription factors such as NKX2-5, MEF2C, HAND2 and MYOCD. Nevertheless, NKX2-5+ hESC-MP derivatives did not form contractile cardiomyocytes, raising questions concerning the suitability of these cells as a platform for cardiomyocyte replacement therapy. Gene profiling experiments revealed that, although hESC-MP derived cells expressed a suite of cardiac related genes, they lacked the complete repertoire of genes associated with bona fide cardiomyocytes. Our results suggest that whilst agents such as TGF-β1 and 5-Azacytidine can induce expression of cardiac related genes, but treated cells retain a mesenchymal like phenotype.